Using Instagram in Teaching English to the Students of SMAN 6 Pinrang - Rahman, Muliana; Jabu, Baso; Sunra, La (Har Press Indonesia, 2023)
This study aims to find out the effectiveness of using Instagram as an English teaching medium. This type of research is experimental research. The design of this study is a pre-experimental design, which uses a one-group pretest-posttest design by only using the pretest and posttest as sources of data without a control group. Between the pretest and posttest, the researcher gave a treatment. The sample in this study was X2 class students, totaling 32 people. In collecting data, the researcher used pretest-posttest, questionnaire, and observation. The results of this research show that the use of Instagram as an English learning medium is effectively able to improve students' abilities in narrative text writing. This is based on the results of data analysis the mean value of students' pretest results is 53.72 and the standard deviation value is 5.572, while on the posttest, students' scores have increased, where the mean is 80.94 and the standard deviation value is 8.140. As for the paired T-test results obtained, the value of Sig. (2-tailed) is less than 0.05 (p =.000).